Comportamento biomecânico de pinos personalizados em remanescente dentário fragilizado - Kasuya, Amanda Vessoni Barbosa (2017)
The objectives of this work were to evaluate the stress distribution (SD), fracture resistance (RF), adhesive strength (AS) and their respective fracture patterns of weekeaned bovine roots, rehabilitated with customized pins with different resinous materials. In addition, the objective of this study was to evaluate the polymerization depth of the resinous materials by Knoop microhardness method (MH). Eight experimental groups were established (n = 10 for FR and AS; n = 5 for MH), with the factor under study: 1. The post type (industrialized glass fiber post relined (I) and personalized post (P), 2. the relining material only for industrialized glass fiber post (experimental composite (e) and composite resin (R)); 3. the material used only for personalized post (experimental composite (e) and bulk fill resin (b), and 4. the amount of remaining dentin (root embrittlement inner wear, in lengths of 5 mm or 10 mm). One hundred and forty bovine roots of similar size were selected and restored according to the group to which they belonged. For FR, Pperiodontal and alveolar bone were simulated and the specimens were placed in an Instron 5965 machine at a 135 ° angle to the long axis and loaded at a constant velocity of 0.5 mm/min in compression until the fracture. The fracture pattern was classified as: F1- crown; F2- root; F3- crown/root; F4- fracture with displacement of the crown/post. For AS, the specimens were sectioned in slices of 1 mm perpendicular to their long axis. Each specimen was placed in a test machine to received the load in the apical-coronal direction, at a constant velocity of 0.5mm / min, pushing the pin through the largest side of the sample until fracture. The fracture pattern was classified as: F1- cohesive of the pin and/or reline material; F2- cohesive of dentin; F3- adhesive of pin/reline material; F4 - Adhesive bonding cement/ eline material and F5 - mixed. For MH, the specimens were sectioned parallel to their long axis. The tests were performed with a Knoop penetrator under a static charge of 50 grams per 10 seconds. MH was calculated as the average value for each third. Finally, the finite element method was used to analyze the DT. 3D virtual models representative of each experimental group were created and analyzed under von Mises equivalent stresses criterion, simulating loading of 100N at a 45o angle with the long axis. The experimental composite proved to be an alternative for the rehabilitation of weakened roots when used to create personalized posts or when used as a relining material, with FR values similar to the traditional technique, but with more favorable stress distributions. Moreover, it presented excellent adhesive strength to the dentin structure, being comparable to conventional composite resin and bulk fill resin. The bulk fill resin resulted in low values of fracture resistance associated with the fracture and displacement of post/crown. Lower microhardness values were observed in the apical third for bulk fill resin.